سد كاريبا بين زامبيا وزيمبابوي وتداعياته 1955-1995 - علي، خالد محمد محمد (جامعة القاهرة - معهد البحوث والدراسات الافريقية, 2021)
تعد المصادر المائية من الثروات الضرورية لاستمرار الحياة، لذلك تم بناء العديد من السدود الكبيرة على الأنهار الدولية، والتي تمنع تدفق مياه فيضان النهر، فتنشأ ورائها البحيرات الصناعية، وتسمى بالخزانات التي تستخدم لأغراض توليد الكهرباء، وتوفير المياه للري والشرب، وغيرها من أغراض، وتخضع عملية بناء السد إلى مجموعة من القوانين المنظمة لاستخدام المياه. إن قضية السدود الكبيرة على الأنهار الدولية من القضايا المهمة لأنها تعد مسألة حياة أو موت بين البلدان المتشاطئة حوله، بل أنها تعد نتيجة مباشرة للتنافس المتزايد على المياه، وهذا بدوره سيؤثر على قضايا السلام والأمن حول الأنهار العابرة للحدود، لهذا وجب على الدول المتشاطئة أن تختار تسوية هذه الخلافات من خلال التعاون وتقاسم المنافع والبعد عن الهيمنة أو السيطرة على موارد المياه. سد كاريبا من السدود الكبيرة التي بنيت بين دولتي زامبيا وزيمبابوي وتم بناءه على نهر الزامبيزي، دون دراسة لآثاره السلبية، والتي أدت إلى نزوح الملايين وإعادة توطينهم، بالإضافة زيادة المشكلات الاجتماعية والاقتصادية والجيولوجية والتي تطلبت إعادة تأهيل السد، والهدف من بناء سد كاريبا هو خدمة صناعة النحاس في المنطقة دون النظر للسكان الأصليين، لهذا وجب على الحكومات الأفريقية عمل الدراسات الاستقصائية قبل بناء شد كبير والاستعانة بالخبراء لتقييم آثار السد. لجأ الباحث إلى أسلوب الرصد والمتابعة التاريخية والتحليل، لمدى تأثير السدود على البيئة الاجتماعية والاقتصادية بالمنطقة المحيطة للسد. Water resources are among the wealth necessary for the continuation of life, so many large dams have been built on international rivers, which prevent the flow of river flood waters, and artificial lakes arise behind them, called reservoirs that are used for the purposes of generating electricity, providing water for irrigation and drinking, and other purposes, and are subject the process of building the dam is based on a set of laws regulating the use of water. The issue of large dams on international rivers is one of the important issues because it is a matter of life and death between the riparian countries around it. Rather, it is a direct result of the increasing competition for water, and this in turn will affect the issues of peace and security around the cross- border rivers. For this reason, the riparian countries must choose Settling these differences through cooperation and benefit-sharing and away from domination or control over water resources. Kariba Dam is one of the large dams that were built between the countries of Zambia and Zimbabwe and was built on the Zambezi River, without studying its negative effects, which led to the displacement and resettlement of millions, in addition to increasing social, economic, geological problems that required the rehabilitation of the dam. Copper is in the area without regard to the indigenous population, so African governments must conduct surveys before building a major dam and seek the assistance of experts to assess the effects of the dam.
Keywords: المصادر المائية -- توليد الكهرباء -- السدود الأفريقية -- بحيرة كاريبا -- الطاقة الكهرومائية